2021
DOI: 10.1177/0363546521988943
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid in Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-analysis

Abstract: Background: Hemarthrosis after anterior cruciate ligament (ACL) reconstruction procedures can delay rehabilitation and have toxic effects on the cartilage and synovium. Tranexamic acid is widely used in adult reconstruction procedures; however, its use in ACL reconstruction is a novel topic of study. Purpose: To analyze the available literature on hemarthrosis, pain, functional outcomes, and complications after administration of tranexamic acid in ACL reconstruction procedures. Study Design: Meta-analysis. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…The meta-analysis published by Johns et al on the same topic, concluded that TXA improves early post-op drain output, hemarthrosis, pain scores, and knee ROM, without increasing the risk of complications, while being cost-effective and clinically effective. 18 Following the additional pooling of 3 new studies in this meta-analysis 15-17 , pain and knee function score improvements J o u r n a l P r e -p r o o f failed to achieve clinical significance leaving only hemarthrosis parameters as being clinically significant. Regarding the risk of complications, findings in this study were similar in that no adverse events were reported in any of the RCTs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The meta-analysis published by Johns et al on the same topic, concluded that TXA improves early post-op drain output, hemarthrosis, pain scores, and knee ROM, without increasing the risk of complications, while being cost-effective and clinically effective. 18 Following the additional pooling of 3 new studies in this meta-analysis 15-17 , pain and knee function score improvements J o u r n a l P r e -p r o o f failed to achieve clinical significance leaving only hemarthrosis parameters as being clinically significant. Regarding the risk of complications, findings in this study were similar in that no adverse events were reported in any of the RCTs.…”
Section: Discussionmentioning
confidence: 92%
“…Regarding the risk of complications, findings in this study were similar in that no adverse events were reported in any of the RCTs. In terms of cost-effectiveness, none of the RCTs, included in either meta-analysis, objectively studied cost-effectiveness; therefore, this conclusion cannot be made at the current time and it is unclear how Johns et al made such a claim about cost 18 . While it is believed that TXA usage in ACLR is likely cost-effective, this is not yet proven.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These discussions included the reduction in the length of time for which the drain will be in situ, and the use of tranexamic acid and other types of pain relief best suited to day-case procedures, with the goal of optimal pain relief and recovery for our cohort of patients. Johns et al (2021) concluded from their study that the use of tranexamic acid in ACLR surgery results in reduced joint drain output and hemarthrosis, and improved pain scores and range of motion in the initial post-operative period, without complications or thromboembolic events [69]. The changes that were introduced because of these discussions led to earlier mobilisation and physiotherapy while ensuring pain was controlled, patient satisfaction was maintained, and ultimately earlier discharge times.…”
Section: Discussionmentioning
confidence: 99%
“…Ó very recently published systematic review and metaanalysis included five trials for analysis. 7 The authors demonstrated a mean reduction in drain output of 61 mL within a 24-hour window postsurgery and improved Lysholm and visual analog pain scores, which extended to 6 weeks postsurgery and reduced the need for joint aspiration. 7 Alkhatib, AINouri, Abdullah, Alzobi, Alkaramany, Sasaki and Ishibashi have added three new randomized controlled trials and performed a new meta-analysis.…”
Section: See Related Article On Page 506mentioning
confidence: 91%